Pathological Findings in Cetaceans Sporadically Stranded Along the Chilean Coast - Alvarado-Rybak, Mario; Toro, Frederick; Abarca, Paulette; Paredes, Enrique; Español-Jiménez, Sonia; Seguel, Mauricio (Frontiers in Marine Science, 2020)
Chile has one of the largest coastlines in the world with at least 50% of the world cetacean species occurring within its jurisdictional waters. However, little is known regarding the health status and main causes of death in cetaceans off continental Chile. In this report, we summarize the major pathological findings and most likely causes of death of 15 cetaceans stranded along the Chilean coast between 2010 and 2019. Drowning, due to fishing gear entanglement, was the most likely cause of death in 3 Burmeister’s porpoises (Phocoena spinipinnis), a Risso’s dolphin (Grampus griseus) and a short-beaked common dolphin (Delphinus delphis). Additionally, the 3 Burmeister’s porpoises had mild to moderate eosinophilic and histiocytic pneumonia with pulmonary vasculitis most likely associated with the nematode Pseudalius inflexus. A fourth Burmeister’s porpoise died of drowning after stranding alive at a sandy beach. Two fin whales (Balaenoptera physalus) died most likely of trauma associated with large vessel collision. A long-finned pilot whale (Globicephala melas) and an Orca (Orcinus orca) stranded most likely due to traumatic intra/interspecific interaction with other odontocete although for the pilot whale, osteoporosis and edentulism could have played a role. For a Strap-toothed beaked whale (Mesoplodon layardi), Dwarf sperm whale (Kogia sima), Southern right-whale dolphin (Lissodelphis peronii), Peale’s dolphin (Lagenorhynchus australis) and a dusky dolphin (Lagenorhynchus obscurus), the cause of stranding could not be determined. This study shows, despite the small number of examined carcasses that in Chile, human related trauma is an important cause of single cetacean stranding events.